1994
DOI: 10.1111/j.1365-2052.1994.tb00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genetic variation in European, African and Indian cattle populations

Abstract: Summary Mitochondrial DNA from representative animals of 13 different cattle breeds was assayed for restriction fragment length polymorphisms (RFLP) to determine phylogenetic relationships and levels of variation among breeds; 16 different mitotypes were found, described by 20 polymorphisms. Within these 16 mitotypes two major lineages were apparent: an Afro‐European and an Asian type. These were found to differ at over 2.3% of sites surveyed. None of the mitotypes found in the Asian lineage was detectable in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 26 publications
(17 reference statements)
2
46
0
3
Order By: Relevance
“…In addition, the average pair-wise sequence divergence of mtDNA among KNC (varying from 0.0005 to 0.0020) is lower than that of mtDNA for any breed of Bos Taurus and Bos Indicus. According to the reports for native populations such as African and Indian cattle breeds, sequence divergences ranged from 0.0011 to 0.0092 [16]. Our results clearly showed that similarity levels of KNC were in a considerable situation showing very low nucleotide diversity (0.0005 to 0.0007) for a few animals.…”
Section: Discussionmentioning
confidence: 56%
“…In addition, the average pair-wise sequence divergence of mtDNA among KNC (varying from 0.0005 to 0.0020) is lower than that of mtDNA for any breed of Bos Taurus and Bos Indicus. According to the reports for native populations such as African and Indian cattle breeds, sequence divergences ranged from 0.0011 to 0.0092 [16]. Our results clearly showed that similarity levels of KNC were in a considerable situation showing very low nucleotide diversity (0.0005 to 0.0007) for a few animals.…”
Section: Discussionmentioning
confidence: 56%
“…A distinctive mtDNA haplogroup, T1, in modern African breeds, with high frequencies in Africa and low ones in the Iberian Peninsula and the Levant, initially led genetics researchers to posit an independent domestication from the wild North African aurochs Edwards et al 2004;Loftus et al 1994b). As will be detailed, this view from the mtDNA evidence has been modified subsequent to whole-chromosome comparisons, but evidence exists for a genetic contribution to African domestic cattle by male African aurochsen.…”
Section: The Genetics Of Cattle In Africamentioning
confidence: 99%
“…Just a few years before the first publications on mtDNA analyses of living African cattle (e.g., Loftus et al 1994b), archaeozoologist Grigson (1991) argued from her comparative osteological studies of ancient wild and domestic cattle from Europe, South Asia, and Africa that ancient and modern skeletal evidence suggested a separate cattle domestication in Africa. Grigson contended that ancient African domestic cattle are so distinct from both taurine and indicine cattle that they could derive from a separate domestication of the northern African aurochs subspecies, B. primigenius opisthonomous.…”
Section: Grigson's Bos Africanusmentioning
confidence: 99%
“…In the present time, these are being replaced by more powerful technologies such as the use of mitochondria DNA 47,48 and molecular markers such as microsatellites and SNPs among others. 49,50 In Tanzania a wide gene pool (a broad diversity of livestock breeds, strains or ecotypes) has not been fully exploited due to inadequate knowledge on their genetic distinctiveness.…”
mentioning
confidence: 99%